Communicating a Conservation-Restoration Project: The Case of Chapel of Original Sin at the Sacro Monte di Varallo - Greta Acuto (Ochrona Dziedzictwa Kulturowego)
The Sacro Monte di Varallo (Sacro Monte of Varallo) is a natural reserve and religious place near Monte Rosa, Piedmont (Italy). Some of the greatest artists of the time worked there to create a representation of the places and events of Christ life with life-size statues and mural paintings, starting from the 15th century. The Conservation and Restoration Center 'La Venaria Reale' carried out a model conservation-restoration project focusing on the conservation of Chapel 1 (which represents the Original Sin). This project was developed as a case study  efforts  to properly communicate the conservation-restoration issued and the work carried out to different audiences. This initiative is part of a broader project, the Interreg Italy-Switzerland 'Main10ance', which aims to develop a sustainable conservation program for the UNESCO Sacro Montes. Communication was carried out on several levels, based on the interest of visitors, through the following avenues:1 - explanatory panels near Chapel 1;2 – explanatory tours with conservators and other professionals;3 – creation of website with information, insights and news dedicated to the work in progress.To create a more effective and engaging communication, information relating to visitors was collected. The public was grouped according to different characteristics in three public targets: Children; Adult; and Blind people. For each, a reference guidelines and a specific narrative was developed:•      to involve children it was decided to use games;•      to address adults, it was decided to focus the discussion on the frequently asked questions posed by visitors;•      to bring the blind public closer, an evocative visit was proposed. Mock-ups were prepared to give the possibility to touch them, in order to make people understand the difference between surface in good condition and in degraded state.